Wage bargaining and the wage drift: Evidence from Finland - Timo Tyrväinen (Bank of Finland, 1991)
This article examines various aspects of the wage drift. It is reaffirmed that in Finland wage drift is closely related to the excess demand for labour. As excess demand for labour indicates that contractual wage is below the equilibrium wage we specify a bargaining model which determines the target wage. This model for equilibrium (real) wages consists of variables influencing profits, on the one hand, and the utility of the union, on the other hand In addition, the relative bargaining power matters. After having described the three-step bargaining process in Finland, an error correction equation for the conditional wage drift is specified with changes in target wages, changes in contract wages and the target-error stemming from the past as independent variables. Several variants of the model are estimated. We conclude that, in Finland, 1) there is a robust inverse correlation between contract wages and the wage drift. The latter acts as an error correcting faetor. The relevant equilibrium wage is generated by the bargaining process described in the paper. 2) the adjustment of wages through the wage drift is not instantaneous. 3) wage drift is contributed by "target errors" stemming from the past periods. 4) the variation in the wage drift appears to be correlated with errors in (inflation) expectations. 5) the wage drift tends to be larger when the dispersion of the economic position of the firms - measured by standard deviation of the stock of orders - is large.
URN:NBN:fi:bof-201808011821
Keywords: 330